New hosts and localities for helminths of carnivores in Argentina - Moleón, María Soledad; Kinsella, John Mike; Moreno, Pablo Gastón; Ferreyra, Hebe Del Valle; Pereira, Javier; Pía, Mónica; Beldomenico, Pablo Martín (Zootaxa, 2015)
A total of 111 samples (43 faeces and 79 gastrointestinal tracts) of 14 wild carnivore species from 12 Argentine provinces were analyzed. Helminth eggs were identified in 73% of the faecal samples and adult worms were recovered from 81% of the gastrointestinal tracts. We found 19 helminth species. Among the most frequent findings were parasites of domestic carnivores, namely Toxocara canis, Toxocara cati, Toxascaris leonina, Ancylostoma caninum, Ancylostoma tubaeforme and Uncinaria stenocephala. In addition, new hosts are reported for 6 nematode species and 5 helminth species are recorded for the first time in Argentina: Aonchotheca putorii, Molineus brachiurus, Cyathospirura chevreuxi, Physaloptera praeputialis and Oncicola martini.